Molecular Perspectives for mu/delta Opioid Receptor Heteromers as Distinct, Functional Receptors - Edmund W. Ong; Catherine M. Cahill (Cells, 2014)
Opioid receptors are the sites of action for morphine and the other opioid drugs. Abundant evidence now demonstrates that different opioid receptor types can physically associate to form heteromers. Understandings of the nature, behavior, and role of these opioid receptor heteromers are developing. Owing to their constituent monomers’ involvement in analgesia, mu/delta opioid receptor (M/DOR) heteromers have been a particular focus of attention. There is now considerable evidence demonstrating M/DOR to be an extant and physiologically relevant receptor species. Participating in the cellular environment as a distinct receptor type, M/DOR availability is complexly regulated and M/DOR exhibits unique pharmacology from that of other opioid receptors (ORs), including its constituents. M/DOR appears to have a range of actions that vary in a ligand- (or ligands-) dependent manner. These actions can meaningfully affect the clinical effects of opioid drugs: strategies targeting M/DOR may be therapeutically useful. This review presents and discusses developments in these understandings with a focus on the molecular nature and activity of M/DOR in the context of therapeutic potentials.